2021
DOI: 10.1371/journal.pntd.0009808
|View full text |Cite|
|
Sign up to set email alerts
|

Predictive markers for the early prognosis of dengue severity: A systematic review and meta-analysis

Abstract: Background Predictive markers represent a solution for the proactive management of severe dengue. Despite the low mortality rate resulting from severe cases, dengue requires constant examination and round-the-clock nursing care due to the unpredictable progression of complications, posing a burden on clinical triage and material resources. Accordingly, identifying markers that allow for predicting disease prognosis from the initial diagnosis is needed. Given the improved pathogenesis understanding, myriad cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 107 publications
2
19
1
Order By: Relevance
“…Dengue has a moderate-to-low mortality rate; however, the mortality rate among severe dengue patients may rise significantly with inadequate clinical management [ 3 ]. Despite growing research on potential severity predictors, no definitive predictors of severe dengue resulting in unwanted hospitalization and fatalities have been identified [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dengue has a moderate-to-low mortality rate; however, the mortality rate among severe dengue patients may rise significantly with inadequate clinical management [ 3 ]. Despite growing research on potential severity predictors, no definitive predictors of severe dengue resulting in unwanted hospitalization and fatalities have been identified [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has noted that thrombocytopenia and elevated AST/ALT in the first 72 hours post fever onset are early predictors of severe dengue [ 33 , 34 ]. However, in our cohort, these variables could not distinguish deterioration to severe dengue in the 3 to 4 days and 1 to 2 days before the onset of severe dengue (data do not show).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 This condition occurs because of the direct and indirect impact of the dengue virus on the bone marrow. 20,21 Due to direct effects in the hematopoietic process, leukopenia can be found at the beginning of DF disease and most viruses. 22 The results of the study showed that 16 infants had leucopenia when they were hospitalized.…”
Section: Discussionmentioning
confidence: 99%